‎ Psychiatric Disorders in Iranian Children and Adolescents - Mohammad Reza Mohammadi (Iranian Journal of Psychiatry, 2016)
Objective: The aim of the present study was to investigate the epidemiology of psychiatric disorders in ‎children and adolescents in five provinces of Iran: Tehran, Shiraz, Isfahan, Tabriz and Mashhad.‎ Method: In the present study, we selected 9,636 children and adolescents aged 6-18 years through ‎multistage cluster random sampling method from Tehran, Shiraz, Isfahan, Tabriz and Mashhad. ‎We instructed the clinical psychologists to complete the Strengths and Difficulties Questionnaire ‎‎(SDQ) for the participants, and those who received a high score on SDQ, completed the Persian ‎version of Kiddie-SADS-Present and Lifetime Version (K-SADS-PL). We used descriptive ‎analysis and 95% confidence interval to investigate the relationship between scores of the K-‎SADS questionnaire and demographic factors‏. ‏We used one-way ANOVA to test the significant ‎differences among the disorders according to sex, age and province of residence.‎‎ Results: Based on the results, oppositional defiant disorder (ODD) (4.45%) had the highest prevalence of psychiatric ‎disorders in the five provinces and substance abuse and alcohol abuse (0%) had the lowest ‎prevalence. In addition, attention deficit hyperactivity disorder (ADHD) had the most ‎prevalence in boys (5.03%) and ODD had the most prevalence in ‎girls (4.05%). Among the three age groups, 6 to 9 year olds had the highest rates of ADHD ‎‎(5.69%); 10 to 14 and 15 to 18 year olds had the highest rates of ODD (4.32% and 4.37% ‎respectively). Among the five provinces, Tehran and Mashhad allocated the highest rates of ODD; Isfahan and Shiraz had the highest rates of ADHD; and Tabriz had the highest rates of social phobia.‎ Conclusion: The current study revealed that the overall frequency of psychiatric disorders based on Kiddie-‎SADS-Present and Lifetime Version (K-SADS-PL) was higher than a similar study. Moreover, in ‎this study, among the five provinces, Tehran and Mashhad allocated the highest rates of ODD; Isfahan and Shiraz had the highest rates of ADHD; and Tabriz had the highest rates of social phobia. Therefore, these percentage ‎of psychiatric disorders in Iran lead us toward a greater use of consultation and mental health ‎services‏.